Monitoring of Butterfly Abundance in the Urban Forests of Cibubur Arboretum and University of Indonesia - Hasni Ruslan; Imran SL Tobing; Dwi Andayaningsih (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Research related to biodiversity that was carried out regularly could be part of monitoring activities to see changes in butterfly populations in an area. Butterflies have a role as environmental bioindicators that were commonly found in various places. Urban forests such as the Cibubur Arboretum and the University of Indonesia were mini conservation sites that were habitats for butterflies. The purpose of this study was to monitor changes in butterfly abundance in the urban forest of Cibubur Arboretum and UI. This research was conducted in 2014 and 2021. This observation was carried out by purposive sampling method. Each urban forest was divided into 3 different stations consisting of 2 plots (20 x 20 m), and repeated 3 times on each plot with an interval of 1 week using a sweeping net and camera. Observations were carried out for 1 hour on each plots. The total observations of butterflies in both urban forests were 18 times. Individual butterflies found in 2014 in the Urban Forest Arboretum Cibubur (339) individuals, and the year 2021 (232) individuals. in the UI City Forest in 2014 898 individuals were found and 269 individuals in 2021. Nymphalidae family was the family with the highest number of individuals found in 2014 and 2021. The individual species found in 2014, included in the category of sporadic, subrecedent, recedent, subdominant and dominant. Meanwhile, the butterfly species found at the study site were categorized into Sub-recedent, Recedent, and Sub-dominant groups in 2021. Differences in vegetation, changes in use, and anthropogenic disturbances could affect changes in butterfly observations.